FAKTOR-FAKTOR MEMPENGARUHI MASYARAKAT GOLPUT DALAM PEMILIHAN KEPALA DESA PULAU TINGGI PERIODE 2017-2023. - Zulian S Zulian S; Sri Erlinda; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This research was conducted in Pulau Tinggi Village, Kampar Subdistrict, Kampar District. This research was motivated by the low level of community participation in the election of the Pulau Tinggi village head for the period 2017-2023. The formulation of the problem in this study is: What was the cause of the community choosing Golongan Putih (White Group) in the election of the Head of Pulau Tinggi Village Period 2017-2023? This study aims to determine the causes of the Golongan Putih (White Group) community in the election of the Head of Pulau Tinggi Village for the period 2017-2023. The population in this study is the Golongan Putih (White Group) community in the election of the Pulau Tinggi Village in the period 2017-2023. The sample in this study amounted to 57 people. Based on the results of the study indicate that there are factors affecting the Golongan Putih community in the election of the head of Pulau Tinggi village for the period 2017-2023. Where there are two factors affecting the abstention community in the election of the head of Pulau Tinggi Village for the period 2017-2023. 1. Apathetic respondent's answer Yes 72.5% while responde answers No 27.5%. 2. Respondent's cynicism Yes 63% while respondent answers No 37%.Keywords : Golongan Putih, Election of Village Heads